Phenotypic and genetic analysis of dysprothrombinemia due to a novel homozygous mutation. Issue 6 (3rd July 2017) - Su, Kankan; Jin, Yanhui; Miao, Zhihai; Cheng, Xiaoli; Yang, Lihong; Wang, Mingshan
ABSTRACT: Objective : We study the phenotype and genotype of a novel gene mutation of factor II (FII) that leads to dysprothrombinemia, and do the meta-analysis to illuminate its molecular pathogenesis. It will further contribute to our comprehension of the pathogenesis of this type of disease. Methods : The prothrombin time (PT), activated partial thromboplastin time (APTT) and the activities of other factors were determined by the one-stage clotting method. The prothrombin antigen was measured with enzyme-linked immunosorbent assay (ELISA). Function of the mutant protein was evaluated by thrombin generation tests. Potential mutations in exons, exon–intron boundaries and 5', 3' untranslated sequences of prothrombin gene were screened by polymerase chain reaction and direct sequencing. Suspected mutations were confirmed by reverse sequencing. The structure change of this protein was analyzed by model and bioinformatics analyses. Results : Phenotypic analysis revealed that the proband had an obviously prolonged PT, APTT, reduced prothrombin activity but normal antigen levels. The other tests were normal. Sequencing analysis detected a homozygous g.26329T>G in the catalytic domain resulting in p.Tyr510Asp. His parents and uncle were heterozygous for this mutation. The thrombin generation test showed that the mutant protein had obstacles in thrombin generation. Bioinformatics and model analyses illuminated that the mutation will be probably damaging and perturbing the structure of Na+-binding site, which will affect the activation of prothrombin. Conclusion : This was the first report of such a mutation in the position which was associated with dysprothrombinemia.